Efficacy of intra-articular injection of combined platelet-rich plasma and hyaluronic acid in knee degenerative joint disease (182). Issue 10 (31st October 2021) - Randelli, Pietro; RANDELLI, FILIPPO; Sciancalepore, Fabio; Fossati, Chiara; Pasqualotto, Stefano; Menon, Alessandra
Objectives: Osteoarthritis (OA) of the knee is a debilitating disease whose prevalence has increased across the world with aging population. Platelet-Rich Plasma (PRP) and Hyaluronic Acid (HA) injections appear to be two of the main strategies for conservative treatment of early knee OA. The effectiveness of both treatments, however, is still under debate because contrasting results have been described in the current literature. Some pre-clinical studies evaluated the association of PRP and HA with encouraging results, highlighting the possibility of a synergistic effect between the two compounds and suggesting a possible use through combined intra-articular injections. The aim of this prospective randomized controlled double-blind clinical trial is to evaluate the efficacy of intra-articular injections of PRP and HA for the treatment of early stages of knee degenerative joint disease in improving joint function and reducing pain, compared to the intra-articular injections of PRP and HA alone. Methods: Patients with knee early OA were prospectively enrolled and then double-blinded randomly divided into three groups of fifty-eight subjects each: HA alone, PRP alone and PRP+HA group. Patients received three intra-articular injections with two-week interval period among each dose. Patients clinical outcome was evaluated through five questionnaires [The Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), Tegner Activity, Visual Analogue Scale (VAS), Knee injury and Osteoarthritis Outcome Score (KOOS), and International Knee Documentation Committee (IKDC) Subjective Knee Form] before the treatment (T0) and after 3, 6 and 12 months from the first injection. Patients'use of paracetamol and supplementary analgesia for knee pain during the study was collected. Results: One hundred and seventy-four patients were enrolled in this study (age, 30-80 years; 108 females and 66 males) and 162 completed the 12-month follow-up. All patients showed significant clinical improvement after treatment. The analysis of covariance (ANCOVA) did not show statistically significant differences among the three groups for all the variables analysed at 6 and 12 months of follow-up (p>0.05).No significant differences were found in terms of adverse events (p=0.49) among the three groups of patients (p=0.92).The demand for paracetamol and supplementary analgesics was generally low and there were no significant differences among the groups (p=0.23 and p=0.56, respectively). Conclusions: Injections treatments for early knee OA are an important conservative therapeutic strategy. To date, the current literature presents many contrasting studies about the effectiveness of PRP or HA, but only a few consider the combined use of PRP and HA as attractive therapeutic option. Our study has not shown any significant difference in clinical and functional outcomes among the three experimental groups, suggesting a substantial equivalence of these three treatments. Thus, cost-effectiveness is in favor of HA injections in the conservative treatment of early OA.